Small Molecules for Chemically Induced Pluripotency Inception (Molecular Medicine Communications, 2023)
Harnessing endogenous transcription factors directly by small molecules for chemically induced pluripotency inception refers to using specific small molecules to activate endogenous transcription factors to reprogram adult cells into induced pluripotent stem cells (iPSCs). This approach aims to bypass the use of viral vectors or genetic manipulation to introduce exogenous factors, making it a potentially safer and more efficient method for generating iPSCs. Jin and colleagues show that small molecule CD3254 activates endogenous existing transcription factor RXRα to significantly promote mouse chemical reprogramming. Mechanistically, the CD3254-RXRα axis can directly activate all the 11 RNA exosome component genes (Exosc1-10 and Dis3) at the transcriptional level. Unexpectedly, rather than degrading mRNAs as its substrates, RNA exosome mainly modulates the degradation of transposable element (TE)-associated RNAs, particularly MMVL30, which is identified as a new barrier for cell-fate determination. In turn, MMVL30-mediated inflammation (IFN-γ and TNF-α pathways) is reduced, promoting successful reprogramming. Collectively, their study provides conceptual advances for translating environmental cues into pluripotency inception, particularly identifies that the CD3254-RXRα-RNA exosome axis can promote chemical reprogramming and suggests modulation of TE-mediated inflammation via CD3254-inducible RNA exosome as important opportunities for controlling cell fates and regenerative medicine. Proc Natl Acad Sci USA. 2023 May 23;120(21):e2215155120.  doi: 10.1073/pnas.2215155120.